Diseño control de interno bajo Metodología Coso I para la gestión de inventario de la empresa Electrigases del Valle (2024)
The Design of Internal Control is essential to safeguard the integrity and efficiency of financial processes. The COSO 1 Methodology stands out as a global framework for implementing effective internal controls, being crucial in inventory management.